Breaking barriers: harnessing hypofractionated radiotherapy to transform outcomes in low tumor mutation burden stage III non-small cell lung cancer - a retrospective study - Yang, Jingyun; Cui, Tianxiang; Zhang, Yang; Chen, Guangpeng; Wang, Xinxin; Sun, Jianguo; Zhang, Anmei; Li, Guanghui (Frontiers in Immunology, 2025)
BackgroundNon-Small Cell Lung Cancer (NSCLC) patients with low tumor mutational burden (TMB) showed low sensitive to conventional fractionated radiotherapy in our previous study. This study aimed to evaluate the efficacy and safety of hypofractionated radiotherapy (HFRT) in locally advanced NSCLC patients with low-TMB compared to conventional fractionated radiotherapy (CFRT).MethodsWe retrospectively analyzed clinical outcomes of 74 locally advanced NSCLC patients with low-TMB undergoing definitive radiotherapy from January 2017 to July 2023, with 31 patients received HFRT (received radiation doses of >2Gy and ≤5 Gy per fraction) and 43 received CFRT (received radiation doses of 1.8-2 Gy per fraction). Progression-free survival (PFS), overall survival (OS) and objective response rate (ORR) to radiotherapy was analyzed in the two groups. Univariate analysis was performed to assess the impact of clinical characteristics on PFS. We also analyzed PFS in subgroups receiving HFRT or CFRT combined with immunotherapy and chemotherapy.ResultsSurvival analysis revealed the median PFS of 13 months in the HFRT group was significantly better than the 10 months in the CFRT group (p = 0.024). The 6-month and 12-month PFS rates were 80.6% and 61.3% for the HFRT group, versus 81.4% and 39.5% for the CFRT group, respectively. Median OS was 27 months in the HFRT group and 20 months in the CFRT group (p = 0.079). There were no statistically significant differences in major adverse events between the HFRT and CFRT groups (all p>0.05). In the subgroup receiving combined immunotherapy and chemotherapy, the median PFS was 10 months in the HFRT group and 9 months in the CFRT group (p = 0.092).ConclusionHFRT was superior to CFRT in prolonging PFS for patients with low-TMB locally advanced NSCLC. It was a safely and effective approach for these patients and was worth further prospective studies with larger sample sizes.